Dampak Penggunaan Teknologi Informasi dan Komunikasi Terhadap Kehidupan Sosial - Arif, Sutan Mohammad (Universitas Serambi Mekkah, 2024)
This research investigates the impact of the use of Information and Communication Technology (ICT) on social life. Through literature and theoretical reviews, this research describes changes in communication patterns, the formation of online communities, and changes in social norms as a result of advances in ICT. Key findings include increased global connectivity, privacy risks and psychological impacts such as digital addiction. The research also details practical implications and potential solutions, such as digital awareness education, policy development, and mental health programs. The conclusion confirms that the use of ICT makes both positive and negative contributions, requiring balance and wise action to maximize its benefits while reducing its risks in modern social life.